"Histological characteristics of HPV‐associated and ‐independent squamous cell carcinomas of the vulva: A study of 1, 594 cases". Issue 12 (31st August 2017) - Rakislova, Natalia; Clavero, Omar; Alemany, Laia; Saco, Adela; Quirós, Beatriz; Lloveras, Belen; Alejo, Maria; Pawlita, Michael; Quint, Wim; del Pino, Marta; de Sanjose, Silvia; Ordi, Jaume; et al.
Abstract : There are at least two different etio‐pathogenic pathways for the development of vulvar squamous cell carcinoma (VSCC): one associated with infection by human papillomavirus (HPV) and another independent of HPV. We aimed to describe the histological characteristics of HPV‐associated and ‐independent tumors and to determine the best strategy to identify HPV in VSCC. A single paraffin block was available for review from a series of 1, 594 VSCCs. In all cases HPV DNA detection was analyzed using the SPF10PCR/DEIA/LiPA25 system and p16 immunohistochemistry (IHC). A tumor was considered as unquestionably HPV‐associated if both HPV DNA and p16 IHC were positive. A tumor was considered indisputably HPV‐independent if both HPV DNA and p16 IHC were negative. Two groups of tumors were classified as non‐conclusive: (1) HPV DNA+/p16− and (2) HPV DNA−/p16+. WHO typing and a thorough histological evaluation were conducted in all cases. Four hundred and forty‐one tumors were HPV DNA+ with 367 cases (23.0%) being HPV DNA+/p16+. The latter tumors were more frequently basaloid or warty (49.8%), but 36.5% were of the keratinizing type; 1, 153 tumors were HPV DNA−, with 1, 060 cases (66.5%) being HPV DNA−/p16−. These HPV DNA−/p16− tumors were mostly keratinizing (81.2%) but were occasionally basaloid or warty (5.2%). The features of HPV DNA−/p16+ cases ( n = 93) were similar to those of the HPV‐associated VSCC, and HPV DNA+/p16− ( n = 74) cases had a more diverse profile, although they were more similar to HPV‐independent tumors. Several histological characteristics were more frequently associated with HPV‐related VSCC (koilocytotic‐like change, necrosis, moderate to marked pleomorphism, invasive front in nests; p < 0.001), however, none of these characteristics allowed differentiation between HPV‐associated and ‐independent VSCC. In conclusion, histological criteria do not allow differentiation between HPV‐associated and ‐independent VSCC. p16 Alone is a clinically easy strategy to determine HPV status in VSCC. Abstract : What's new? Today, most pathologists use clinico‐pathological criteria to classify vulvar tumors as human papillomavirus (HPV)‐associated or HPV‐independent. However, a comprehensive study analyzing histological characteristics of HPV‐positive and ‐negative carcinomas has yet to be conducted. Here, the authors set to describe the histological characteristics of HPV‐associated and ‐independent tumors and determine the best strategy to identify HPV‐associated tumors in a large series of 1, 594 vulvar cancers. They show that histological criteria do not allow differentiation between HPV‐associated and HPV‐independent neoplasms, and that p16 immunohistochemistry alone is an easy clinical strategy to determine HPV status in vulvar cancer.